Measuring adolescents’ level of interest in nature: a promising psychological factor facilitating nature protection - Neurohr, Anna-Lena; Pasch, Nadine; Otto, Siegmar; Möller, Andrea (Frontiers in Psychology, 2023)
Studies indicate that young people are more prepared to engage in pro-environmental behavior if they are interested in nature and recognize it as worthy of protection. However, a reliable instrument to measure adolescents’ interest in nature is still lacking. Therefore, we developed a new metric, the Scale of Interest in Nature (SIN). It consists of 18 items, is based on Item-Response-Theory and was validated using the known group approach (N = 351 adolescents). Results indicate that adolescents’ interest in nature correlates positively with their connection with nature, their intention to preserve nature and engagement in pro-environmental activities in their free time. Bivariate Pearson correlations between the SIN and the Connectedness to Nature Scale (INS), as well as the Environmental Values model (2-MEV) demonstrated the scale’s construct validity. Hence, the SIN scale provides an economical way to measure adolescents’ interest in nature in research contexts or environmental and sustainability education settings.